Selection and association of resistent varieties of corn with Beauveria bassiana for control of Sitophilus zeamais (Coleoptera: Curculionidae) - Potrich, Michele (2010)
This work had as objective to associate control strategies to minimize the damage caused by Sitophilus zeamais in corn. Corn cultivars, resistant and susceptible to insect, were submitted to tests, with and without choice. Then, the selected cultivars were associated with the fungus Beauveria bassiana (Unioeste 4 and Esalq 643 isolates), before and after S. zeamais infestation. It was verified that the cultivar CD 3121 presented resistence, increasing the duration of the egg-adult cicle, decreasing the number of emerged insects and decreasing the weight loss of the grains, and showed non-preference to feeding by the insect, when compared to cultivar CD 307. The association caused an increase in the duration of the egg-adult cycle, decreasing of the number of emerged insects, decreasing percentage damaged grains and decreasing weight loss, for both cultivars CD 3121 and CD 307, and for both isolates. On the other hand, the isolates association with cultivars CD 3121 had a better control of S. zeamais.